1962
DOI: 10.4141/cjps62-032
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Irrigation Treatments on Yields and on Fertilizer Utilization by Sweet Corn and Snap Beans

Abstract: A range in each of the nutrients – nitrogen, phosphorus and potassium – was applied to an infertile Podzol soil in a split-plot experiment receiving the following sprinkler irrigation treatments: 1) "none", natural rainfall; 2) "minimum", 1 inch per irrigation during the critical stage of flowering to harvest; 3) "optimum", 1 inch per irrigation throughout the crop season; and 4) "excess", 2 inches per irrigation whenever 3) was applied.Both crops responded to irrigation during the flower to harvest stage but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

1967
1967
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
1
9
1
Order By: Relevance
“…This confirmed that dry beans are more sensitive to water stress after the flowering stage than preflowering. Similar results were reported by other researchers for beans (MacKay and Eaves, 1962;Robins and Domingo, 1956;Dubetz and Mahalle, 1969) and other crops (Heatherly, 1993;Westgate, 1994;Ney et al, 1994). Negative effects in the preflowering stage can be compensated for by adequate irrigation after flowering.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This confirmed that dry beans are more sensitive to water stress after the flowering stage than preflowering. Similar results were reported by other researchers for beans (MacKay and Eaves, 1962;Robins and Domingo, 1956;Dubetz and Mahalle, 1969) and other crops (Heatherly, 1993;Westgate, 1994;Ney et al, 1994). Negative effects in the preflowering stage can be compensated for by adequate irrigation after flowering.…”
Section: Discussionsupporting
confidence: 91%
“…A high irrigation regime (S 1 : irrigation to field capacity when available water decreased to 75% of field capacity) gave the highest yield in all years. This result was inconsistent with other irrigation response studies on beans (Maurer et al, 1969;Burman and Bohmont, 1961;MacKay and Eaves, 1962;Smittle, 1976;Miller and Burke, 1983) and peas (Maurer et al, 1968). The S 1 and S 2 irrigation regimes were both in the best performing group in high rainfall years, while S 1 out-yielded S 2 in low rainfall years.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This work has shown that in timothy, as in cereals (Penman, 19626;Mackay & Eaves, 1962;Bingham, 1966;Roebuck & Peeler, 1966) the yield of seed can be increased by irrigation. However, there was no indication of a higher requirement for nitrogen where plots were irrigated, as was found in the work with cereals, and in the third year of the present work irrigation did not increase yield where nitrogen had been applied.…”
Section: Discussionmentioning
confidence: 99%
“…Although irrigation of herbage grasses grown for production of seed has commanded little previous attention, there is considerable evidence on the effects of irrigation and moisture stress on yields of grain from cereals. Penman (1962), MacKay & Eaves (1962), Bingham (1966), and Roebuck & Peeler (1966) have reported positive responses to irrigation, and have drawn attention to the increased requirement for nitrogen under irrigation. A reduction in grain yield following soil moisture stress has been frequently recorded (van der Paauw, 1949;Asana, Saini & Ray, 1958;Denmead & Shaw, 1960;Robins & Domingo, 1962;Lehane & Staple, 1962;Chinoy, 1962;Aspinall.Nicholls & May, 1964).…”
mentioning
confidence: 99%